P035 Female white collar workers remain at high risk of breast cancer after adjustment for individual risk factors related to reproduction and lifestyle. (1st September 2016) - Kullberg, Cecilia; Selander, Jenny; Wiebert, Pernilla; Albin, Maria; Borgqvist, Signe; Plato, Nils; Manjer, Jonas; Gustavsson, Per
Abstract : Background: Breast cancer is the most common cancer in women worldwide and the incidence is steadily increasing in Sweden. Hormones play an important role in breast cancer aetiology and many of the established risk factors are related to endocrine change in the body. Previous studies have shown differences in breast cancer risk between occupational groups, although without the possibility to control for reproductive and lifestyle factors. Aim: The aim was to investigate how much of variation in breast cancer incidence between occupations that could be explained by risk factors related to reproduction and lifestyle. Method: Data for this study was obtained from the Malmö Diet and Cancer study, a population cohort study. 14 109 women, born 1923–1950, were followed from 1991–2013. Self-administered questionnaires were answered in regard to lifestyle and reproductive risk factors. Hazard ratios were estimated for occupational groups and compared with and without adjustments for reproductive and lifestyle factors. Preliminary results: White collar workers were at higher risk of breast cancer than blue collar workers. After adjusting for reproductive and lifestyle risk factors the risk for white collar workers were decreased while the risks for blue collar workers were increased. Registered nurses had a significantly higher risk of breast cancer, (HR = 1.48 95% CI = 1.07–2.05) also after adjusting for confounding factors, (HR = 1.49 95% CI = 1.07–2.08) compared to all other occupations. Teachers in theoretical subjects had a higher risk of breast cancer (HR = 1.57 95% CI = 1.06–2.32) in the crude model which decreased after adjustments (HR = 1.35 95% CI = 0.89–2.05), indicating that the excess risk were caused by reproductive and lifestyle risk factors. Conclusion: Female white collar workers, including registered nurses, remain at high risk of breast cancer after adjustment for individual risk factors related to reproduction and lifestyle.